Entrance to the Versova Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
Versova's colloquial name is Vesave, which derives from the Marathi-Konkani word for rest (as in, a resting place for ships and seafarers), likely connected to its importance as a harbor.